Application of Plackett-Burman Experimental Design for Lipase Production by Aspergillus niger Using Shea Butter Cake - Salihu, Aliyu (ISRN Biotechnol, 2013)
Plackett-Burman design was used to efficiently select important medium components affecting the lipase production by Aspergillus niger using shea butter cake as the main substrate. Out of the eleven medium components screened, six comprising of sucrose, (NH(4))(2)SO(4), Na(2)HPO(4), MgSO(4), Tween-80, and olive oil were found to contribute positively to the overall lipase production with a maximum production of 3.35 U/g. Influence of tween-80 on lipase production was investigated, and 1.0% (v/w) of tween-80 resulted in maximum lipase production of 6.10 U/g. Thus, the statistical approach employed in this study allows for rapid identification of important medium parameters affecting the lipase production, and further statistical optimization of medium and process parameters can be explored using response surface methodology.